TRANSMISI HARGA GABAH TERHADAP HARGA BERAS: TINJAUAN ARAH, BESARAN DAN LAMA PERUBAHAN - Agung Andiojaya (JSEP (Journal of Social and Agricultural Economics), 2021)
Policies to maintain rice prices are a sensitive policy in Indonesia so that the government controls the rice price tightly in every level of the rice market. To make sure it runs well, the government needs to take into account the magnitude, direction, and speed of transmission of the rice price changes. When these three things can be monitored and controlled well, the success rate of controlling prices is in hand. This study investigates the direction and speed of transmission of changes in grain prices at the farm level to changes in rice prices at various levels of trade. The empirical results utilizing Granger Causality Test and VAR indicate that changes in the price of grain at the farm level significantly cause changes in rice prices at the milling and wholesale levels in a unidirectional way. Meanwhile, there is a piece of additional information where changes in the retail price of rice significantly cause changes in the price of grain at the farm level rather than vice versa. By implementing the IRFs method reveal the transmission’s duration of price change takes place in the short term and long term. Considering these findings, the policy of stabilizing rice prices at the mill and wholesale levels should be implemented immediately when the price of farmers' grain begins to change.